Rancang Bangun Sistem Informasi Pengelolaan Surat Masuk Dan Surat Keluar Perusahaan - Eka Wulansari Fridayanthie; Aan Fauzi (Paradigma, 2019)
Based on Government Regulation No.77 of 2012: Public Company (Perum) Organizing Agency for Indonesian Aviation Navigation Services (LPPNPI) or better known as AirNav Indonesia is a business entity that provides aviation navigation services in Indonesia in the form of State-Owned Enterprises (SOEs). LPPNPI or AirNav Indonesia has 5 Directorates and 5 Non-Directorateates, one of which is the Corporate Secretary (Corporate Secretary), which has 3 units, one of which is the BODs unit and protocol, each of which has a well-organized archive of incoming and outgoing mail. , to maximize work in managing incoming and outgoing mail, it is necessary to manage web-based incoming and outgoing mail records that can arrange incoming and outgoing mail, especially at the Corporate Secretary in Protocol Protocol BODs. Keywords: Information System Design, Management of Entry and Exit Letters